Is it the decision of women to choose a cesarean section as the mode of birth? A review of literature on the views of stakeholders - Alice Yuen Loke; Louise Davies; Yim-wah Mak (BMC, 2019)
Abstract Background A debate on the decision of women to choose a cesarean section as the mode of birth in uncomplicated pregnancies from the views of relevant stakeholders. Main text Using five electronic databases, a literature search was conducted for studies published from January 2003 to December 2016. Studies on a woman's right to request or to choose a cesarean section as the mode of birth in uncomplicated pregnancies were included. Fifty-five articles were identified (39 research studies and 16 opinion-based articles). Among health professionals, obstetricians were the most supportive of this right. It is argued that although women reported wanting to choose the mode of birth, with the safety of their babies as the priority, they also relied on the advice of their maternity care provider and considered it the responsibility of their obstetrician to make the decision. A higher proportion of the general public in countries with well-developed private healthcare accepted that a woman should have the freedom to choose the mode of birth. Conclusions This review provided a debate on the choice of pregnant women in uncomplicated pregnancies on the mode of birth from various stakeholders. Further research is required to explore what the meanings of autonomy of pregnant women to choose the mode of birth, and the process that they go through when making this decision.